Prevalence and Genotype Distribution of Human Papillomavirus Infection Among 40,613 Women: An Outpatient-Based Population Study in Kunming, Yunnan - Zhang, Yu; Xu, Ya; Dian, Ziqin; Zhang, Guiqian; Fan, Xin; Zhao, Yuan; Sun, Yi (Frontiers in Public Health, 2022)
Human Papillomavirus (HPV) infection is one of the most common sexually transmitted infections worldwide. The current study aimed to investigate the prevalence and genotype distribution of HPV infection among outpatient-based populations. A total of 40,613 women were recruited from the First People's Hospital of the Yunnan Province. Our study retrospectively analyzed the results of cervical HPV screening among 40,613 women. The results of study showed the prevalence and genotype distribution of HPV infection was different among various outpatient-based populations, and the prevalence of HPV infection was the highest in the gynecological outpatients (26.59%), followed by reproductive gynecological outpatients (18.51%), and the prevalence of physically examined population was the lowest (8.15%). The outpatient-based population was facing a huge threat of HPV infection, especially women from the gynecology clinic. The three most common HPV genotypes were HPV-52 (4.79%), 16 (2.95%) and 58 (2.83%). However, the distribution of HPV genotype varied by populations, especially in physically examined population, the infection rate of HPV-81 ranked third among all infections with various genotypes. Two peaks of prevalence of HPV infection were observed among women under 25 years (31.93%) and over 55 years (28.55%), while the prevalence in women aged 46–55 years (20.18%) was the lowest. Our study on the prevalence and genotype distribution of HPV infection among various outpatient-based populations will provide scientific evidence for vaccination strategies of HPV and prevention and control plans of cervical cancer in Kunming area.